An Assessment System For Teaching English Using Gamification In The Era Of Digitalization (Eurasian Journal of Humanities and Social Sciences, 2025)
The article examines the principles and assessment criteria in teaching English to students in the context of the digitalization of education. Special attention is given to the role of gamification as an innovative tool for motivation and knowledge control. The author analyzes modern assessment approaches adapted to game-based learning methods and proposes criteria that meet the requirements of the digital era.